Entrepreneurship Orientation and Innovation Capability: The Role of Intellectual Resources as Mediation (A Case Study of SMEs Furniture in Madiun East Java) - Ardianus Laurens Paulus (School of Business, IPB University (SB-IPB), 2018)
The utilization of intellectual resources in business is growing rapidly today. It is characterized by creative ideas emerging from organizations and companies that are competing in all areas. This research aims to examine the influence of entreprenuership orientation toward innovation capability mediating by intellectual resources. This research employs a quantitative approach using survey method. Data collection was conducted at 61 Small and Medium Enterprises (SMEs) Furniture located in Madiun area, East Java from February to July 2017. The data were analyzed using measurement model of structural equation modeling supported by partial least square (PLS) 3.0 software. This study shows that entrepreneurship orientation has a positive and significant effect on intellectual resources and innovation capability, while the influence of intellectual resources has no effect on innovation capability. The result of mediation testing of intellectual resources as mediator between entrepreneurship orientations and innovation capability is not proven in this research.Keywords: intellectual resources, entrepreneurship orientations, innovation capability, furniture, PLS